Impact of Dietary Protein Source on Muscle Performance: An in-vivo Behavioral Assay (OR26-05-19). (13th June 2019) - Putra, Christianto; Rimkus, Barbora; Shehaj, Andrea; Gage, Matthew; Konow, Nicolai; Mangano, Kelsey
Abstract: Objectives: To analyze the impact of different sources of protein (pea, whey or casein) on functional muscle performance in C57BL/6 mice. Methods: A total of 21 mice were randomized to protein intervention groups. Mice were individually caged in a temperature controlled and 12-h light-dark cycle room. Subjects were randomly assigned to casein, whey, and pea protein sourced diets, matched by sex. Total energy (3.77 ± 0.04 kcal/g) and macronutrient composition (% of total energy: carbohydrate 66%, protein 18% and fat 16%) were matched across diets. Body weight and amount of food consumed was measured weekly. Functional muscle performance was measured by forelimb grip strength test using an Accuforce Cadet Force Gage and hanging test using Kondziela's inverted screen test capped at 600 seconds (at intervention week 9). The recorded strength and hang time measurements were corrected for body-mass. Data processing and analyses were performed in IBM SPSS Statistics 25. Results: Excluding 2 mice due to outliers, the total number of mice per group were: casein (n = 9), whey (n = 6), and pea (n = 5). No baseline differences in body weight or average amount of food consumed per week were observed between groups. However, mice on the pea protein diet gained significantly more weight (8 ± 2g) compared to whey (4 ± 2g) and casein (2 ± 2g) diet groups ( P  < 0.007). Mice fed with whey protein sourced diets showed significantly stronger maximum fore limb grip strength (237 ± 21g) compared to pea (200 ± 7g) and casein (219 ± 26g) fed mice ( P  < 0.005). Body-mass corrected average and maximum grip strength tests showed that mice consuming pea protein sourced were significantly weaker compared to the casein protein sourced diet group, but not to whey protein sourced diet group (Table 1). Conclusions: No observable differences were found between whey and casein in functional muscle performance of C57BL/6 mice when corrected for body weight. However, the pea sourced protein diet resulted in higher weight gain and weaker functional muscle performance measurements. Funding Sources: University of Massachusetts Lowell Seed Grant (NK, KM, MG). Supporting Tables, Images and/or Graphs: